Optimization of formula sustained releaase captopril tablet using factorial design method - Melinda Pratiwi; Lannie Hadisoewignyo (Universitas Gadjah Mada, 2010)
Captopril is one of the most frequently used medicine in the treatment of hypertension with repeatedly used frequency in a day. Therefore captopril should be formulated in the form of sustained release and find the optimum formula. The purpose of this study was to determine the influence of both factors and their interactions, which are the ratio of polymer HPMC K4M -xanthan gum factor at the level of 1:1 and 4:1 and the concentration of tartaric acid at levels of 0% and 5% on physical properties of tablets, drug release, floating lag time. Furthermore, find the optimum formula that meets the requirements and produce tablets with drug release pattern according to zero order kinetics. Based on Design Expert optimization program was obtained the optimum formula using a combination of polymer HPMC K4M - xanthan gum ratio 3.75:1 and concentration of of tartaric acid 4.5% would be result the hardness respons 12.02 Kp the friability 0.47%, the floating lag time 0.32 minutes, and the rate of dissolution 0.05 mg/min. The results show that combination of factors polymer HPMC K4M - xanthan gum ratio can increase the tablet hardness, lower tablet friability, accelerate the floating lag time, and increase the rate of dissolution. Tartaric acid can decrease the tablet hardness, increase the friability, accelerate the floating lag time, and increase the rate of dissolution. Interaction of both can reduce the tablet hardness, increase the tablet friability, slow floating lag time, and increase the rate of dissolution.